Iridium‐Catalyzed Asymmetric Allylic Dearomatization by a Desymmetrization Strategy - Wang, Ye; Zheng, Chao; You, Shu‐Li (Angewandte Chemie International Edition, 2017)
A desymmetrization strategy was developed involving iridium‐catalyzed allylic dearomatization of indoles. The six‐membered‐ring spiroindolenines contain three contiguous stereogenic centers, including an all‐carbon quaternary center, and were obtained in up to 99 % yield with 99 % ee and >95:5 d.r. When treated with a catalytic amount of tosylic acid, six‐membered spiroindolenine undergoes an unprecedented six‐to‐seven‐membered ring expansion, affording the corresponding hexahydroazepino[4,5‐b]indole. The Legend of Spiro: An iridium‐catalyzed desymmetrization reaction involving allylic dearomatization of indoles was developed. The six‐membered‐ring spiroindolenines were obtained in up to 99 % yield with 99 % ee and >95:5 d.r. When treated with a catalytic amount of tosylic acid, six‐membered spiroindolenine undergoes six‐to‐seven‐membered ring expansion, yielding hexahydroazepino[4,5‐b]indole.